Answer:
Simplifying
(6x + -4z)(6x + 4z) = 0
Multiply (6x + -4z) * (6x + 4z)
(6x * (6x + 4z) + -4z * (6x + 4z)) = 0
((6x * 6x + 4z * 6x) + -4z * (6x + 4z)) = 0
Reorder the terms:
((24xz + 36x2) + -4z * (6x + 4z)) = 0
((24xz + 36x2) + -4z * (6x + 4z)) = 0
(24xz + 36x2 + (6x * -4z + 4z * -4z)) = 0
(24xz + 36x2 + (-24xz + -16z2)) = 0
Reorder the terms:
(24xz + -24xz + 36x2 + -16z2) = 0
Combine like terms: 24xz + -24xz = 0
(0 + 36x2 + -16z2) = 0
(36x2 + -16z2) = 0
Solving
36x2 + -16z2 = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '16z2' to each side of the equation.
36x2 + -16z2 + 16z2 = 0 + 16z2
Combine like terms: -16z2 + 16z2 = 0
36x2 + 0 = 0 + 16z2
36x2 = 0 + 16z2
Remove the zero:
36x2 = 16z2
Divide each side by '36'.
x2 = 0.4444444444z2
Simplifying
x2 = 0.4444444444z2
Take the square root of each side:
x = {-0.666666667z, 0.666666667z}
Explanation: You don't need to explain with words, by doing this work you explained how to simplify and how you can do it in many ways to get the exact answer.